Relações políticas e tradição romana na retórica empregada por Agostinho na obra De Civitate Dei (412-426) - Lima, Bruno Soares (2018)
The present study analyzes the book De Civitate Dei written by Augustine of Hippo between 412–426 CE according to some aspects of political relations and Roman traditions related to discursive rhetoric and emphasizing view on Rome as the “City of God”. The problem formulated questions the structure and function of rhetoric in the book, under the hypothesis that an ideal Rome was constructed in the text written by Augustine to meet the goal of to defending Christians against the accusation from the non-Christian Romans, that claimed the invasion of Rome was the fault of the Christianism. The aim of this study is to show the construction of the Roman traditions and of the political relations in Augustine’s rhetoric as an approach to the document to discuss historical aspects of the De Civitate Dei through the theoretical and methodological contributions of Social History. This discussion will be based on concepts developed by Max Weber, Serge Berstein, Roger Chartier e Pierre Bourdieu and . It makes use of the methodology of French discourse analysis according Maingueneau